A user guide to the GF/CF diet : for autism, Asperger syndrome and AD/HD - Jackson, Luke, 1988- (Jessica Kingsley, 2002)
What is the GF/CF diet? Does it work? What's it like to go on it? In this user guide to the gluten and casein free diet, Luke Jackson, who is 12 years old and has Asperger Syndrome, tells you everything you need to know - both good and bad.